Exploring the Aspect of Silencing of Subaltern Voices and Marginalization Through Textual Analysis of Water (2006) By Bapsi Sidhwa - Aziz, Mussarat; AKHTAR, SADIA (JELLL, 2025)
This research examines Bapsi Sidhwa’s Water (2006) through a postcolonial lens to explore its representation of subaltern women in colonial India. Basically the research explores by focusing on widows residing in a religious ashram, that how the novel depicts their experiences while exposing the systemic techniques of suppression and marginalization. The research states of employing Gayatri Chakravorty Spivak theory, Sidhwa portrays these women as experiencing double repression due to patriarchal dominance, religious traditions that are firm, and neglect of colonial authorities. The depiction of widowhood as societal death, intensified by economic exploitation, the effects of caste systems and ceremonial isolation. While the colonial context offers some background, it fails to confront these injustices, while worsen the women’ plight. . By placing the experiences of the widows at the crossroads of patriarchy, religion, and imperialism, this study adds to the wider conversation on postcolonial literature and feminist theory, stressing the ongoing difficulty of representing marginalized voices.